2010
DOI: 10.1590/s0100-83582010000100009
|View full text |Cite
|
Sign up to set email alerts
|

Weed community and growth under the canopy of trees adapted to the brazilian semi-arid region

Abstract: The objectives of this work were to evaluate the floristic composition and dry biomass of weeds under the canopy of seven perennial species adapted to the Semi-Arid region of Brazil, and correlate these characteristics with growth traits of the perennial species. The following perennial species were evaluated in two experiments (E1 and E2): mesquite (Prosopis juliflora), jucá (Caesalpinia ferrea), white popinac (Leucaena leucocephala), mofumbo (Combretum leprosum), neem (Azadirachata indica), sabiá (Mimosa cae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
(7 reference statements)
1
4
0
Order By: Relevance
“…A smaller number of species was found as compared with similar studies (Sit et al, 2007;Silva et al, 2010a) but the number of more frequently occurring conformed to these studies.…”
Section: Planting Densitiessupporting
confidence: 63%
See 1 more Smart Citation
“…A smaller number of species was found as compared with similar studies (Sit et al, 2007;Silva et al, 2010a) but the number of more frequently occurring conformed to these studies.…”
Section: Planting Densitiessupporting
confidence: 63%
“…Weed effects on the behavior of trees have been observed by some authors (Cantarelli et al, 2006). However, tree crops may also influence the understory (Silva et al, 2010a). There are three other aspects under which the tree-understory species relationship has been studied; these aspects provide information that is useful for weed control: silvopastoral systems, allelopathy, and natural ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Phytosociology and floristic surveys were more predominant with regard to species conservation, with C. leprosum being cited in eight studies (Lacerda & Barbosa, 2020;Lima & Coelho, 2018;Pereira, et al, 2018;Sabino et al, 2016;Lima & Coelho, 2015;Umetsu et al, 2011;Silva et al, 2010;Farias & Castro, 2004). Studies that address knowledge about the floristic composition and phytosociological structure of a species or locality allow the conservation, management and recovery of natural environments (Borém & Ramos, 2001;Velazco et al, 2015).…”
Section: Conservation Regeneration and Managementmentioning
confidence: 99%
“…Studies associated with environmental regeneration cite C. leprosum as a facilitator in the establishment of species in the semiarid region (Vieira et al, 2013;Lucas et al, 2022a;Lucas et al, 2022b) and weed growth (Silva et al, 2010). In these studies, it was observed that species that grow under the canopy of C. leprosum present better values in water status, lower incidence of solar radiation, lower thermal stress and higher soil relative humidity (Vieira et al, 2013;Lucas et al, 2022a;Lucas et al, 2022b).…”
Section: Conservation Regeneration and Managementmentioning
confidence: 99%
“…However, such associations may become hampered in the event that the associated tree exhibits some level of allelopathy, or the capacity to alter the availability of soil nutrients, light and other limiting resources. On the other hand, the growth performance of any tree may be affected by a number of factors including cultural practices, planting density, as well as the tree's interaction with understory plants that also significant from an ecological viewpoint (Cantarelli et al 2006, Leopold and Salazar 2008, Silva et al 2010.…”
Section: Introductionmentioning
confidence: 99%